RATE AND INDICATIONS OF ELECTIVE AND EMERGENCY CAESAREAN SECTION; A STUDY IN A TERTIARY CARE HOSPITAL OF PESHAWAR - Naeem, Mohammad; Khan, Muhammad Zia Ul Islam; Abbas, Syed Hussain; Khan, Ayasha; Adil, Muhammad; Khan, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2015)
Background: The study was conducted to determine the rate and clinical indications for emergency and elective caesarean section. Methods: This was a cross-sectional descriptive study conducted from December 2010 to January 2011 in Gynaecology unit-A of Lady Reading Hospital Peshawar. Consecutive patients who gave birth in the hospital during the study period were included in the study. There were a total of 966 patients. Mode of delivery and basic demographics of the patients who underwent elective and emergency caesarean section were noted down. Clinical indications were recorded. Results: Out of 966 patients, 210 underwent caesarean section. Therefore, the rate of caesarean section was 21.7 per 100. Among those 78% (n=164) were emergency caesarean sections and others were elective caesarean sections. Top six indicators for caesarean sections were foetal distress 17.1 % (n=36), obstructive labour/failure to progress 16.1% (n=34), previous caesarean section 15.2% (n=32), breech presentation 9.5% (n=20), cephalopelvic disproportion 6.1% (n=13), failed induction 5.7% (n=12) and pregnancy induced hypertension (PIH) 5.7% (n=12). Conclusion: The rate of caesarean section was only slightly higher than recommended by the WHO. Most of caesarean sections were emergency caesarean sections. Keywords: Caesarean section, rate, indications, Elective, Emergency